2021
DOI: 10.1080/17482631.2021.1959496
|View full text |Cite
|
Sign up to set email alerts
|

A healthy view? exploring the positive health perceptions of older adults with a lower socioeconomic status using photo-elicitation interviews

Abstract: Purpose: The health perceptions of older adults with a lower socioeconomic status still seems to be unsettled. To gain more insight in these perceptions, 19 older adults were interviewed with the use of a photo-elicitation method. Methods: Participants reflected on ten photographs covering aspects of physical, social and mental health, and were also asked if and how they experience to have control over their health. Results: The results showed that the perception of health depended on the background of the par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
0
3
0
1
Order By: Relevance
“…According to them, the conceptualisation of health depends on contextual factors and scientific perspectives [ 9 , 39 , 66 ]. They also emphasise that people construct their own understandings of health based on personal circumstances and individual characteristics [ 9 , 27 , 32 , 39 , 55 , 64 , 66 ]. For example, these articles highlight that people from lower socio-economic backgrounds have a more disease-oriented approach to health and focus on different aspects of health compared to other groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to them, the conceptualisation of health depends on contextual factors and scientific perspectives [ 9 , 39 , 66 ]. They also emphasise that people construct their own understandings of health based on personal circumstances and individual characteristics [ 9 , 27 , 32 , 39 , 55 , 64 , 66 ]. For example, these articles highlight that people from lower socio-economic backgrounds have a more disease-oriented approach to health and focus on different aspects of health compared to other groups.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, they recommended paying attention to the cultural sensitivity of the PH concept and method when applying it to non-Western populations [ 73 ]. Likewise, some studies advised that attention should be paid to aligning the PH method to suit vulnerable groups—including disadvantaged individuals and the sometimes frail elderly—as the literature indicates they may have a lower awareness of how their behaviour can influence their health and they may put a greater emphasis on illness than on health aspects [ 27 , 32 , 55 , 64 ]. Finally, a primary care evaluation study reported physicians noting the prevalence of interpretations of PH among professionals.…”
Section: Resultsmentioning
confidence: 99%
“…Het meeste wetenschappelijke onderzoek wordt juist gedaan met mensen die prettig ouder worden. Gelukkig zijn er uitzonderingen, zoals Carlsson et al (2023); Joshi & Bailey (2023); Leyerzapf et al (2018); en Platzer et al (2021). Ook opvallend is dat veel geografisch gerontologisch onderzoek plaatsvindt in westerse landen: de vergrijzing is daar tot nu toe het sterkst.…”
Section: Wonen Welzijn En Zorg In Een Vergrijzende Samenlevingunclassified
“…Photo-elicitation interviews refer to the idea of using photographs in research interviews to explore a certain topic and the photographs can be generated by either the researcher or the research person [ 38 ]. The method has recently been used to involve older people in research [ 39 , 40 ] but as highlighted in a review of the photovoice method with older persons [ 41 ], visual research methods can be practically challenging due to ethical issues, functional and visual impairment, logistics, and resources allocated to the research project. The review further suggests that visual methods need accommodation to different contexts [ 41 ], but there has been little attention to the potential benefits of photo-elicitation interviews as a participatory research method with people living in residential aged care facilities.…”
Section: Introductionmentioning
confidence: 99%